Integrated direct air CO2 capture and solid oxide electrolyzer for sustainable chemical production: Case studies of methanol and synthesis fuel - Mohammadali Emadi; Vahid Barahimi; Eric Croiset (Journal of CO2 Utilization)
This paper presents a comprehensive study of a novel system aimed at producing chemicals from CO2 captured from the atmosphere by integrating direct air capture (DAC) and solid oxide electrolysis cell (SOEC). Two case studies for the chemical produced were considered: CO2 to methanol and CO2 to synthetic fuel (synfuel). All scenarios were based on a DAC system capturing 250,000 tonnes per year of CO2 from the atmosphere. Using Aspen Plus, the results revealed insights into energy consumption, resource utilization, and economic viability. The system produced 36.4 tonne/hr of methanol and 15.1 tonne/hr of synfuel. Methanol production requires 403 MW of electricity and 10.9 tonne/hr of natural gas, with a specific energy consumption of 26.0 kWh/kg-MeOH. Synfuel production demands higher utility usage of 53.9 kWh/kg-synfuel (360 MW electricity, and 7.09 tonne/hr of natural gas). Economic analysis shows a total annual cost and levelized production cost for methanol of $346 M/year and 1.32 $/kg, respectively; for synfuels, the values are $301 M/year and 2.78 $/kg, respectively. Environmental analysis indicates that the amount of CO2 captured per product unit is for synfuel 1.88 kg-CO2 captured/kg-synfuel, and for methanol 0.58 kg-CO2 captured/kg-MeOH. Using Ontario's grid and natural gas emission factor, emission for methanol production amounts to 31.1 g-CO2-eq/MJ-MeOH, while for synfuel, it stands at 5.2 g-CO2-eq/MJ-synfuel. However, these emissions can be notably reduced by transitioning to renewable sources of electricity and can even become negative in the case of synfuel when hydropower and wind are used as electricity sources.